The Role of North Africa in the Emergence and Development of Modern Behaviors: An Integrated Approach - (:unkn) unknown (My University, 2017)
This special issue of African Archaeological Review, entitled BThe Role of North Africa in the Emergence and Development of Modern Behaviors: an Integrated Approach, is the outcome of a session held at the 23rd Society of Africanist Archaeologists (SAfA) meeting held in Toulouse, France, from June 26 to July 2, 2016. Development of our session at the 23rd SAfA meeting in 2016 was motivated by recent advances in several disciplines, including anthropological, cultural, and environmental studies concerned with the importance of North Africa in understanding of the emergence, development, or decline of early and recent anatomically modern humans and associated innovations.
Keywords: African Research